Landownership in the countryside of Portugal and wildfires: a qualitative approach - Rocha, Flávia Suguimoto da (2020)
Every year in the summer, the news about wildfires happening somewhere in Portugal reaches the world through the media (RTP, 2017; Publico, 2019), and when the winter arrives, everything is fine again, but the cycle repeats itself. One of the issues is the excess of fuel in the lands to feed the fire due to the lack of management of lands in the countryside of continental Portugal; more precisely in the Center and North of the country, where the lands are so small, they lost their value for production. More than 80% of the lands in Portugal are privately owned, and different from other countries, there is no concentration in the ownership (Tirapicos, 2019). This exploratory qualitative research is an attempt to understand the reasons behind the lack of use of land, one of the factors that influence those repetitive cycles. Data gathering was made through field trips for observation, data given by the stakeholders, interviews with specialist and, mainly, interviews with landowners. Interviews with the landowners made for this research shed light that the lands on insights of why keeping a land that is unproductive or not profitable. There is more than just emotional attachment, they are part of the identity of those people (Moore, 2014).